PERGESERAN FILOSOFIS MOTIVASI KONSUMSI MUSLIM: ANALISIS DARI MASLAHAH KE HEDONISME DI ERA DIGITAL - Siska Putri; Syukri Iska; Fandi Ahmad Marlion; Azifah Hidayati; Miftahul Jannah (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2025)
ABSTRACT The shift in Muslim consumption motivation from Maslahah to Hedonism is a philosophical shift that is not merely an individual moral issue, but a logical consequence of the adoption and internalization of digital media architecture. This study aims to examine the philosophical shift in Muslim consumption motivation from Maslahah orientation (transcendent welfare) to Hedonism consumption patterns in the Digital Era. This study uses a Systematic Literature Review (SLR) approach to 20 core articles by analyzing how digital mechanisms reduce ethical values ​​in Islamic Economic Philosophy (FES). The results show three main mechanisms of this shift. First, there is a reduction in the Maslahah Episteme, where the concept of Maslahah is compromised from an objective collective goal (Eudaimonia) to subjective instant utility, weakening the principles of Iqtishad and Qana'ah. Second, Digital Algorithms function as determinants of Hedonism, programming desires and exploiting impulse buying through e-commerce, which systematically threatens Hifz al-Aql. Third, the Commodification of Muslim Identity (Halal Hedonism) provides spiritual legitimacy for status-based consumer behavior (flexing), damaging niyyah and triggering Riya'. The conclusion confirms that this shift is a Critical Crisis of Maqasid Syariah which proves the failure of reactive FES in facing systemic mafsadah. Therefore, this study recommends the need for transformation towards a Proactive Maqasid framework integrated into digital architecture design.